KALIMAT TANYA DALAM BAHASA INGGRIS DAN BAHASA LOLODA SUATU ANALISIS KONTRASTIF - Pangi, Yunansi (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research Â entitled â€œInterrogative Sentences in English and Loloda Languageâ€ is an attempt to analyze and describe Â English and LolodaÂ  Language Â focus on interrogative sentences in relation to their forms and functions in both languages.The data of English language are collected from several books, internet, and some theories that relatedÂ  to this research, whereas the data of LolodaÂ  language are collected by interviewing from some informants who know well about this language by using contrastive analysis approach. The data then analyzed and described. to find out the form and functionof interrogative sentence uses the concept of Frank (1972).To compare these two languages, the writer uses Ladoâ€™s (1957 ) concept. He said that contrastive analysis is a way to compare language elements in term of form, meaning, and distribution, in finding the differences and the similarities of both languages. The result of this research shows that English and Loloda language have similarities and differences. The similarities of two languages are found in form of interrogative sentences such as who, why, what, where, when, how (in English); nango, okia, moruoka, kiaka, idoa, sokonoke ( in Loloda) and function of question word of both languages. The differences between two languages are found, such as placing of question words,Â  using Â â€œwhoâ€ , taq questions and structure of sentence. Â  Keywords: Interrogative Sentences, English and Loloda Language. Contrastive Analysis